Perceived Creativity Fostering Teacher Behavior and Student Engagement in Statistic Course: Academic Self Efficacy as Mediator - Atikah Ainun Mufidah; Rose Mini Agoes Salim; Frieda Maryam Mangunsong Siahaan; Shahnaz Safitri; Astri Setiamurti; Maridha Normawati (Journal of Innovation in Educational and Cultural Research, 2023)
Students avoid statistics class because they believe it is tough, however, the topic will be easier to understand if they participate in the learning process. The purpose of this research is to discover the relationship between perceived creativity fostering teacher behavior and student engagement, as well as the role of academic self-efficacy as a mediator in statistics courses for undergraduate psychology students. This is a quantitative study that uses mediation analysis. The data was collected using the University Student Engagement Inventory, the Perceived Creativity Fostering Teacher Index, and the College Academic Self-Efficacy Scale, with 533 participants. The participant criteria were Bachelor of Psychology students who had completed and passed the Statistics course no more than three semesters before filling out the survey questionnaire. The findings reveal that the perceived creativity fostering teacher behavior has an effect on SE through the academic self-efficacy variable. However, because perceived creativity fostering teacher behavior can directly influence self-efficacy, there is a partial mediation effect between variables. This study implies that one way to improve students' involvement in statistics learning is to increase perceived creativity fostering teacher behavior and self-efficacy.